2019
DOI: 10.33225/pec/19.77.55
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Geogebra When Teaching Linear Functions Using the Ipad

Abstract: There is concern about mathematics success and its related pedagogy. Society has seen rapid changes in the economy and technology with a call for these changes to be reflected within the classroom. New methods of teaching mathematics are being sought with the purpose to improve teaching and learning while making mathematics relatable to the new generation of learners. The incorporation of technology within the classroom has been seen an option to make this change. The purpose of this research was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
9
0
5
Order By: Relevance
“…Takači, Stankov, & Milanovic, 2015 Collaborative learning; constructivism; mathematics; function; problem solving The statistical analysis proves that the students' learning achievement in examining functions and drawing their graphs is better when they use GG İpek et al, 2014 Mathematics instruction; geometry education; CAS; computer-assisted geometry education; TPACK; GG Nineteen participants have high academic success while seven have less and only one contributor had previously heard about GG software Therefore, GG is user-friendly and free software that promotes high-order thinking. Critical thinking may help students to solve the questions correctly with the help of the software, it encourages collaborative learning, construction of knowledge, problem solving, and helps students' learning achievement (Misrom et al, 2020;Mudaly & Fletcher, 2019) in examining functions and drawing a better graph with the use of GG as well as in TPACK (Takači et al, 2015) and mathematics instruction with CAS (İpek et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Takači, Stankov, & Milanovic, 2015 Collaborative learning; constructivism; mathematics; function; problem solving The statistical analysis proves that the students' learning achievement in examining functions and drawing their graphs is better when they use GG İpek et al, 2014 Mathematics instruction; geometry education; CAS; computer-assisted geometry education; TPACK; GG Nineteen participants have high academic success while seven have less and only one contributor had previously heard about GG software Therefore, GG is user-friendly and free software that promotes high-order thinking. Critical thinking may help students to solve the questions correctly with the help of the software, it encourages collaborative learning, construction of knowledge, problem solving, and helps students' learning achievement (Misrom et al, 2020;Mudaly & Fletcher, 2019) in examining functions and drawing a better graph with the use of GG as well as in TPACK (Takači et al, 2015) and mathematics instruction with CAS (İpek et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These papers were examined to detect the objectives of the study. The keywords related to GeoGebra and other technological interventions as used in the previous findings, among others, include the following: (i) GeoGebra assisted students effectively in solving the properties of straight-line graph problems (Mudaly & Fletcher, 2019). (ii) The outcomes of the post-test indicate that 70-75% of students answered the questions correctly with the intervention of the GG software (Aizikovitsh-Udi & Radakovic, 2012).…”
Section: Data Extractionmentioning
confidence: 99%
“…[48] investigated the effect of integrating GeoGebra in linear functions and found that learners who were taught linear functions using GeoGebra performed better than learners who were taught the same topic using "chalk and talk". [48] further attest that GeoGebra is effective in teaching linear algebra where the gradient and y intercept of a line may be investigated. Of great assistance, was [14] who designed various GeoGebra applications where teachers and learners can experiment and learn about solving quadratic equations.…”
Section: Effectiveness Of Geogebra In Algebramentioning
confidence: 95%
“…Los estudios mencionados en el marco teórico ya muestran resultados sobre la incidencia de los SGD en la amplificación del ambiente de aprendizaje y en la inmersión en los diversos sistemas de representación, lo cual influye directamente en el desarrollo de los procesos centrales de pensamiento matemático. Existen incluso reportes específicos sobre el empleo de GeoGebra (Santos-Trigo et al, 2019, Mudaly & Fletcher, 2019Olsson, 2019;Zulnaidi, Oktavika, & Hidayat, 2020).…”
Section: Recursos Para El Aprendizajeunclassified